Nación, historia y canon literario en la prensa decimonónica. El «Siglo de Oro» visto por los románticos - Mercedes Comellas (Cahiers de Civilisation Espagnole Contemporaine)
The paper introduces the R&D research project titled The institution of the «Siglo de Oro». Construction processes in the periodical press (1801-1868) (SILEM III), part of the Spanish National Research Plan, which brings together forty researchers from Spanish and European universities to explore, through an interdisciplinary approach blending historical and literary perspectives, the significant role of the nineteenth-century periodical press in shaping one of the foundations of Spanish literary historiography: the «Golden Age». This concept was instrumental in the construction of the liberal nation, relying on literary history—a nascent disciplinary field at the time—and the press as vehicles for disseminating liberal-bourgeois ideologies. The study demonstrates this through a variety of case studies, aiming to provide a representative sample of the richness of our research field. It examines how the golden institution was disseminated during this period on a journalistic and nationalist model that always used romanticism as a mirror in which to look at itself and with which to compare itself.